Overall diet quality and proinflammatory diet in relation to risk of obstructive sleep apnea in 3 prospective US cohorts - Liu, Yue; Tabung, Fred K; Stampfer, Meir J; Redline, Susan; Huang, Tianyi (The American journal of clinical nutrition, 2022)
Inflammation-related mechanisms may be important in the development of obstructive sleep apnea (OSA), and diet plays a crucial role in modulating inflammation. Current epidemiologic evidence for the associations between dietary patterns and OSA risk is limited to cross-sectional studies. We investigated prospectively the associations of overall diet quality and proinflammatory diet with OSA risk. We followed 145,801 participants in the Nurses' Health Study (NHS) (2002-2012), NHS II (1995-2013), and Health Professionals Follow-up Study (1996-2012). Alternative Healthy Eating Index 2010 (AHEI) and Empirical Dietary Inflammatory Pattern (EDIP) scores were calculated based on validated FFQs administered every 4 y. Cox models were used to estimate HRs and 95% CIs. We documented 8856 incident OSA cases during follow-up. In pooled analyses adjusted for potential confounders, higher diet quality (higher AHEI scores) was associated with lower OSA risk (HR comparing the highest with the lowest quintile of AHEI: 0.76; 95% CI: 0.71, 0.82; P-trend < 0.001), and higher dietary inflammatory potential (higher EDIP scores) was associated with significantly increased risk (HR comparing the highest with the lowest quintile of EDIP: 1.94; 95% CI: 1.81, 2.08; P-trend < 0.001). Additional adjustment for metabolic factors attenuated both associations. The association with AHEI score was no longer statistically significant (comparable HR: 0.98; 95% CI: 0.91, 1.05; P-trend = 0.54), whereas the association with EDIP score remained statistically significant (comparable HR: 1.31; 95% CI: 1.22, 1.41; P-trend < 0.001). A healthier diet, particularly one with anti-inflammatory potential, was associated with lower OSA risk.